2019
DOI: 10.3389/fimmu.2019.01815
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight Into the Activation of the NLRP3 Inflammasome by Neisseria gonorrhoeae in Macrophages

Abstract: Gonorrhea is a type III legal communicable disease caused by Neisseria gonorrhoeae (NG), one of the most common sexually transmitted bacteria worldwide. NG infection can cause urethritis or systemic inflammation and may lead to infertility or other complications. The NACHT, LRR, and PYD domains-containing protein 3 (NLRP3) inflammasome is a protein complex composed of NLRP3, apoptosis-associated speck-like protein and caspase-1 and is an important part of the cellular machinery controlli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 63 publications
4
31
0
Order By: Relevance
“…Results obtained by Dey et al have previously shown that bone marrow-derived mice macrophages lacking NLRP3 exhibited increased ROS-production and increased ability to limit Trypanosoma cruzi infection compared to wild-type macrophages 55 . NLRP3 knockout macrophages have also been shown to increase phagocytosis of Neisseria gonorrhoeae 56 and deletion of NLRP3 enhanced neutrophil phagocytosis in a polymicrobial sepsis mouse model 57 . The underlying mechanism for the enhanced phagocytosis was found to be associated with increased expression of macrophage receptor with collagenous structure (MARCO) and mannose-binding lectin (MBL) on the surface of NLRP3 knockout neutrophils 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained by Dey et al have previously shown that bone marrow-derived mice macrophages lacking NLRP3 exhibited increased ROS-production and increased ability to limit Trypanosoma cruzi infection compared to wild-type macrophages 55 . NLRP3 knockout macrophages have also been shown to increase phagocytosis of Neisseria gonorrhoeae 56 and deletion of NLRP3 enhanced neutrophil phagocytosis in a polymicrobial sepsis mouse model 57 . The underlying mechanism for the enhanced phagocytosis was found to be associated with increased expression of macrophage receptor with collagenous structure (MARCO) and mannose-binding lectin (MBL) on the surface of NLRP3 knockout neutrophils 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous study demonstrated that gonococcal activated the NLRP3 inflammasome in THP-1 cells ( Duncan et al, 2009 ; Li et al, 2019 ). The IL-1β ( Figure 2D ), IL-18 ( Figure 2E ) levels in the vaginal secretions in intact group were significantly higher than that observed in control group on the 5th day after inoculation.…”
Section: Resultsmentioning
confidence: 95%
“…Inflammatory stimuli (such as TLRs activation) trigger the initiation of NLRP3 inflammasome by activating NF-κB, thereby inducing IL-1β and NLRP3 mRNA expression ( Dinarello, 2009 ). Although previous studies have shown that lipooligosaccharide (LOS) can induce the pro-inflammatory cytokines through the TLR4-NF-κB pathway ( Packiam et al, 2014 ; Casson et al, 2015 ), a recent study indicated that the first signal of the gonococciinduced-NLRP3 inflammasome activation was not dependent on TLR4, or TLR2 ( Li et al, 2019 ). Strain MS11, an Opa positive strain, was showed to increase the IL-1β secretion in neutrophil ( Sintsova et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infection can ascend, causing salpingitis, pelvic inflammatory disease (PID), bacteremia, and it can cross the endothelial barrier even disseminated gonococcal infection (DGI) [6]. The pathogenesis of gonorrhea is regulated by macrophages, dendritic cells, neutrophils, T cells, epithelial cells and cytokines [7].N. gonorrhoeae has multiple virulence factors like lipooligosaccharide (LOS), type IV pili, opacity associated (Opa) proteins, and an outer membrane porin PorB, that among other roles will help the bacteria to survive in the presence of serum.…”
Section: Introductionmentioning
confidence: 99%